Uranium. No. 04. Interview with Larry Coady - Memorial University of Newfoundland. Extension Service (Community Learning Centre, 1977)
Larry Coady of the Federal Environment Protection Service talks about the environmental hazards posed by uranium mines and what controls are necessary for protection.